2018
DOI: 10.1097/01.aoa.0000547290.01272.9d
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Women’s Intention to Request a Labor Epidural Analgesia, Actually Delivering With Labor Epidural Analgesia, and Postpartum Depression at 6 Weeks: A Prospective Observational Study

Abstract: (Anesth Analg. 2018;126:1590–1597) At the Beilinson Campus of the Rabin Medical Center in Petach Tikva, Israel, a proportion of women who intend to deliver with labor epidural analgesia (LEA) are often unable to receive it due to a lack of available nursing staff, labor rooms, or anesthesiologists at the time of request. As there is no study to date that has specifically examined the relationship between birth plan, satisfaction with LEA, and development of postpartum depression (PPD), the authors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…A few trials showed that untreated pain is associated with a risk of PPD [36,37]. The usage of painkillers can help decrease the incidence of PPD in some cases [38,39]. Our study implied postpartum pain as another risk factor for PPD in the PE group.…”
Section: Discussionsupporting
confidence: 47%
“…A few trials showed that untreated pain is associated with a risk of PPD [36,37]. The usage of painkillers can help decrease the incidence of PPD in some cases [38,39]. Our study implied postpartum pain as another risk factor for PPD in the PE group.…”
Section: Discussionsupporting
confidence: 47%
“…The lack of association between pain intensity during labor and persistent pain and postpartum depression may therefore partly be caused by a ceiling effect. Nevertheless, the literature is inconclusive when it comes to these associations; some suggest that there is an association [10] and that better pain management during birth could prevent postpartum depression [9,11,41], whilst others do not find any preventive effects of analgesia [12,13,37]. The conflicting findings could be related to methodological issues as mentioned, but could also be related to differences in medical procedures in the various clinics.…”
Section: Associations Between Labor Pain and Postpartum Pain/depressionmentioning
confidence: 99%
“…Some studies suggest there is an association between labor pain and postpartum depression, suggesting that managing labor pain and early postpartum pain decreases the risk for depression [8][9][10]. A recent study even suggest that effective labor pain management with epidural analgesia was associated with reduced postpartum depression symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women often have desires and preferences regarding having a certain mode and type of birth and the extent to which these expectations are fulfilled must be accounted for when examining the contribution of mode and place of birth to birth satisfaction. For example, epidural pain analgesia uptake itself is not as influential to birth satisfaction as the fulfilment of the wish to have a medicated or unmedicated birth [ 16 , 17 ]. Maternal and infant complications during birth such as postpartum haemorrhage, vaginal lacerations, and low Apgar scores have also been found to increase negative appraisals of birth [ 12 , 18 ].…”
Section: Birth Satisfactionmentioning
confidence: 99%